Increase of Effectiveness of Organizational and Legal Regulation of State and Municipal Management in Rostov Oblast by Realization of the Concept of Creation of the Center of Emergencies Management - KUROCHKIN, Andrey V.; RADACHINSKY, Yuri N. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
Nowadays, quick development of information technologies in the sphere of state and municipal management is observed in the Russian Federation. Unfortunately, not all of them could be integrated into the unified regional information system. The electronic systems used in municipalities of Rostov Oblast do not ensure quick response to various life situations. They do not allow making quick managerial decisions on the issues of provision of public services. These drawbacks could be overcome by solving a complex of socio-economic issues of municipal entities in the region through formation of a comprehensive complex system of emergencies management.
Keywords: administrative law; municipal law; electronic region; municipal management; information technologies; state service; municipal service